Desenvolvimento de um sistema web para monitoramento de sensores - Santos, Robinson Donizete da Silveira (2015)
There is a large and growing number of intelligent devices connected to the Internet, providing data for the most varied applications. This is the meeting for the Internet of Things, which allows any device to be connected to the Internet. The use of these devices reflects the major trend of the modern world, collect, store and process the greatest possible amount of data in order to produce relevant information. This context creates a moment of opportunity in a multi-billion dollar market. Aware of this startups and large companies are developing platforms for the collection, storage and data analysis. This work is inserted in this context by providing an alternative, a web system developed on the Java platform with the Play Framework aid, which allows the collection, storage and sensor data visualization.